DAYA ANTELMINTIK EKSTRAK ETANOL BIJI SRIKAYA (Annona squamosa L.) TERHADAP CACING Ascaridia galli SECARA In Vitro DAN PROFIL KLTNYA - riyanta aribawa; atiq fauziyah; mustofa mustofa (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2008)
ABSTRACTCustard apple (Annona squamosa L.) is one of efficacious medical plant that often used by local community for constipation, insectiside, carbuncle, scabies, gastrointestinal problem such diarrhoea, dysentery and anthelmintic. In Indonesia, worm disease is infection disease that still high prevalention. Although modern anthelmintic is in stock, but still common community is to use medical plant, specialy custard apple for therapeutic worm disease. The aim of this research was to deterinate anthelmintic capability of ethanol extract of seed custard apple on the worm Ascaridia galli on in vitro. This researches were pure experimental by using Lamson and Brown method submerges that have been modified by using 270 of worm femele, that devided into 9 groups treatment, which was 4 groups for ethanol extract of seed custerd apple in concentration of 10 mg/mL, 20 mg/mL, 30 mg/mL, 40 mg/mL, 4 positive control groups (citrate piperazinae 2 mg/mL, 4 mg/mL, 6 mg/mL, 8 mg/mL) and negative control group (NaCl 9 mg/mL). Each group consist of 6 petri disc and each petri disc contain 5 of worm and 25 mL solution. Anthelmintic capability is measurement observed is the mortality time rate of the worm and value LC50, that is concentration is needed for killing 50% worm population and than analysed date by one way ANOVA and continued by Least Significant Difference (LSD) test. The research result, shown that mortality time rate of worm after submerges by ethanol extract of seed custrad apple in concentration 10 mg/mL, 20 mg/mL, 30 mg/mL, and. 40 mg/mL is 43,33; 38,00; 37,66 and 34,33 hours. Exactly after submerges by citrate piperazinae 4 mg/mL shown mortality time rate of worm is 34,33 hour. LC50 value of ethanol extract of seed custard apple and piperazinae citrate at 12th hour is 36,94 mg/mL and 2,26 mg/mL. Result Thin Layer Chromatography (TLC) shown seed custard apple containes compounds such as from alkaloid, flavonoid and tanin. That compounds is posibility efficacious anthelmintic. Keywords : Annona squamosa L., anthelmintic, Lamson and Brown method submerges.